PENGARUH PENAMBAHAN TEPUNG TEMPE TERHADAP KADAR PROTEIN, SIFAT FISIK DAN ORGANOLEPTIK TIWUL INSTAN - Siti Aminah (JURNAL LITBANG, 2004)
Besides used a staple food by some of sosiety of central of Java, tiwul also represent traditional food which still vended in traditional markets. Recently the role of tiwul in replace of rice is progressively getting attention when some disaster lcnock over some of Indonesia people that is needing food stock specially the source of carbohydrate. Upon which alternative food specially in emmergency moment require to be paid attention the composition of its nuftient and the rlurable product form. Addition of flour of tempe in making of instan tiwul cun improve protein rete.The best treotment of protein rate, nuture of ph,vsicul und orgunolelttic ohtuined by addition of Jlour of tempe 20 %Key words: Tempe mill, traditional food and tiwul